Penguatan Moderasi Beragama Berbasis Kearifan Lokal Manirat Masyarakat Batak di Desa Lumban Siagian Jae, Kec. Siatas Barita, Kab, Tapanuli Utara, Prov. Sumatera Utara - Jungjungan Simorangkir; Bestian Simangunsong; Megawati Manullang; Tiffany Tamba (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Univesitas Kristen Indonesia, 2024)
Abstract This community service article describes the implementation and results of a program to strengthen religious moderation using a local wisdom approach in the Batak community in Lumban Siagian Jae Village, Siatas Barita District, North Tapanuli Regency, North Sumatra Province on July 29 2023. The main purpose of community service this is to help develop a deeper understanding of manirat local wisdom values ​​as a basis for religious moderation. This program involves collaboration between the service team and the local community in designing and implementing a series of activities. This activity includes seminars and mandates that focus on developing the community's economy through local culture and inclusive understanding of religion and interfaith tolerance. The results of this article show that through the manirat local wisdom approach, the Batak people in Lumban Siagian Jae Village can better understand and apply moderation in their religious and cultural practices. Local wisdom values ​​such as mutual respect, cooperation, and openness to religious differences have proven effective in strengthening religious moderation at the community level. This article also notes the positive response from the community towards the community service program, indicating continued potential for further development. This article provides insights for community service practitioners, religious educators, and other communities about the importance of utilizing local wisdom in promoting religious moderation and interfaith harmony. Keywords: Religious Moderation, Manirat, Community Service